THE LEGACY OF ACADEMICIAN A.I. SOBOLEVSKY IN THE SCIENTIFIC CULTURE OF RUSSIA (160TH ANNIVERSARY OF HIS BIRTH) - O V Nikitin (Rusistika (Moskva. Online), 2017)
The article examines the legacy of the outstanding Russian linguist academician A.I. Sobolevsky (1857-1929), one of the founders of the historical study of Russian literary language and diachronic lexicography. As a representative of the traditional comparative studies he made a number of discoveries in the field of Slavic Philology and dialectology, etymology and paleography. Academician A.I. Sobolevsky contributed to the cause of public education and in the study of complex problems of the Ethnology of Slavs. His works are based on rich factual material and contain new linguistic information, they are still the authoritative in an academic and scientific practice and are examples of a historical-linguistic analysis of ancient texts. In the work, along with philological emphasis, we have presented a panorama of the social, historical and cultural events and circumstances that were involved academician A.I. Sobolevsky: we talk about a complex period of academic activities during the October revolution, about his classes and worries and overall perception of the new social environment that is alien to the classical Professor of the old school. The facts stated in the article, first open almost chronicle pages of the severe trials that befell the pre-revolutionary academic science, which tried to preserve the best traditions of Russian Philology.